The Importance of Physical Activity in the Process of Successful Ageing - An Overview - Michalina Kuska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
Rising life expectancy of the populations living in highly developed countries has been observed over recent decades. The number of people worldwide above the age of 60 is increasing at an unprecedented pace. The purpose of the study was to determine the significance of physical activity of older people in the process of successful ageing. Research methods. This article is a review of Polish and foreign studies considering the relationship between physical activity and successful ageing. The elaboration refers to the results of surveys published in the reviewed scientific journals including empirical studies mainly based on diagnostic survey. Study results. A thorough analysis identified three parts: the concept of successful ageing, the relationship between physical activity and health, and physical activity of older persons in Poland compared to their counterparts abroad. A review of the literature and documents has revealed that one of the main factors affecting successful ageing is physical activity. Conclusions. Physical activity and successful ageing are different in the assessed communities. Thus, it is necessary to monitor physical activity of older people in the context of successful ageing - in order to provide conducive circumstances to activating this social group and thus reducing social security cost.